2020
DOI: 10.23969/trikonomika.v19i2.1776
|View full text |Cite
|
Sign up to set email alerts
|

Export Analysis: Authority of Inflation and Exchange Rate in Asean-8

Abstract: This study was aimed to analyze the relationship of long-term and short-term equilibrium between exchange rates and inflation on exports in ASEAN-8 countries (Brunei Darussalam, Laos, Indonesia, Malaysia, Singapore, Philippines, Vietnam and Thailand) by using analysis model with the Autoregressive Distributed Lag (ARDL) panel from the period 1990 to 2017. The model selection was based on long-term and short-term capabilities with different stationary levels. The results revealed that in long-term the exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Exports activity strongly influence the economic growth positively directly (coefficient: 4.21E-07), and became one of the most important determinant factors of economic growth (Y=C+I+G+(X-M). This finding is in line with the previous study revealed that export in goods and services by ASEAN countries, especially the "five" one will expand their international market and production capacity which in turn will lead to the increase of foreign direct investment, job creation, and finally GDP per capita [6], [10], [15], [18]. ASEAN commitment to always reduce trade barriers and improve investment conducive for the last 53 years has been successful to boost export activity and economic growth and it should be improved as fast as possible.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Exports activity strongly influence the economic growth positively directly (coefficient: 4.21E-07), and became one of the most important determinant factors of economic growth (Y=C+I+G+(X-M). This finding is in line with the previous study revealed that export in goods and services by ASEAN countries, especially the "five" one will expand their international market and production capacity which in turn will lead to the increase of foreign direct investment, job creation, and finally GDP per capita [6], [10], [15], [18]. ASEAN commitment to always reduce trade barriers and improve investment conducive for the last 53 years has been successful to boost export activity and economic growth and it should be improved as fast as possible.…”
Section: Discussionsupporting
confidence: 92%
“…It is also can influence economic growth by mediated by the exchange rate. Popular thought said that inflation is always negatively affecting the economy of a country and this study just strengthened the theory [6], [16], [32], [33]. Moderate and high inflation make the prices of many products in the market increase lowering the purchasing power of the people.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations